Penerapan Program Pengembangan Kewirausahaan pada Mahasiswa di Universitas Islam Negeri Sumatera Utara - Arpin Dalimunthe; Zuhrinal M.Nawawi (Masyarakat Ekonomi Syariah Bogor, 2022)
The implementation of the Entrepreneurship Development Program (PPK) at Kanjuruhan University in Islam Negeri Sumatera Utara is expected to achieve the objectives of: (1) creating start-ups and independent new entrepreneurs, (2) improving business management skills for industrial communities, (3) creating entrepreneurship training methods suitable for students , (4) creating business units that can generate profit as a source of generating revenue from Islam Negeri Sumatera Utara University, and (5) opening or providing employment. The stages in implementing the PPK include: (1) Dissemination of the PPK program, this socialization is carried out through announcements on campus boards, campus websites, and social media (Student groups and Alumni Groups). (2) Participants register before they enter as a PPK tenant. (3) Following a written test to see the scientific potential possessed about the world of entrepreneurship, followed by interviews to find out the motivation and seriousness of participants in the PPK program. (4) The results of the selection will determine 20 best value people as prospective tenants. (5) Participants must fill out the willingness sheet to complete the PPK program to completion. Whereas specifically to be achieved are: the growth of an entrepreneurial culture in campus, increased ability to prepare business plans, development of products that have been produced by tenants after participating in PPK activities, the creation of innovative and renewable products. The program will be implemented in a participatory manner with knowledge transfer methods from the proposing team, business experts, UMKM players to PPK tenants through education and training, business simulations, internships, intensive assistance, preparing business plans, and applying business to the tenants' potential and talents. Keywords: Technopreneurship, Entrepreneurship, Tenant